Long-term bisphosphonate treatment coupled with ovariectomy in mice provokes deleterious effects on femoral neck fracture pattern and modifies tibial shape. (1st September 2020) - Monzem, Samuel; Ballester, Rafael Y.; Javaheri, Behzad; Poulet, Blandine; Sônego, Dábila A.; Pitsillides, Andrew A.; Souza, Roberto L.
Abstract : Aims: The processes linking long-term bisphosphonate treatment to atypical fracture remain elusive. To establish a means of exploring this link, we have examined how long-term bisphosphonate treatment with prior ovariectomy modifies femur fracture behaviour and tibia mass and shape in murine bones. Methods: Three groups (seven per group) of 12-week-old mice were: 1) ovariectomized and 20 weeks thereafter treated weekly for 24 weeks with 100 μm/kg subcutaneous ibandronate (OVX+IBN); 2) ovariectomized (OVX); or 3) sham-operated (SHAM). Quantitative fracture analysis generated biomechanical properties for the femoral neck. Tibiae were microCT scanned and trabecular (proximal metaphysis) and cortical parameters along almost its whole length measured. Results: Fracture analyses revealed that OVX+IBN significantly reduced yield displacement (vs SHAM/OVX) and resilience, and increased stiffness (vs SHAM). OVX+IBN elevated tibial trabecular parameters and also increased cortical cross-sectional area and second moment of area around minor axis, and diminished ellipticity proximally. Conclusion: These data indicate that combined ovariectomy and bisphosphonate generates cortical changes linked with greater bone brittleness and modified fracture characteristics, which may provide a basis in mice for interrogating the mechanisms and genetics of atypical fracture aetiology. Cite this article: Bone Joint Open 2020;1-9:512–519.